AKTUALISASI PEREKONOMIAN INDONESIA DALAM PRESIDENSI G20 PELUANG BERTUMBUH ATAU TREN? (STUDI ANALISIS EKONOMI) - Agus Sukawiyana; Anak Agung Elik Astari; Ni Luh Indiani (Nusantara Hasana Journal, 2022)
This study will describe how the actualization of the Indonesian economy in the G20 Presidency, whether it is a Growth Opportunity or a trend only. At the 2019 G20 Osaka Summit which was attended by the President of the Republic of Indonesia, Indonesia was elected as Chair of the G20 in 2023. The G20 presidency is responsible for leading the direction of decision making at the G20 Forum in response to global economic development. As the chair of the G20 in 2023, Indonesia needs to consider priority agendas that reflect the interests of developing countries and are in line with national interests. The purpose of this analysis is to examine national strategic issues that can become a priority agenda for the Indonesian trade sector and for the success of Indonesia's Presidency in 2023. The methodology used is a policy evaluation analysis method using Fundamental Public Impacts to analyze if public policies succeed or failed by looking at 3 (three) fundamental dimensions: Policy, Legitimacy, and Action. To see if public policies succeed or failed, an assessment is carried out on each of the sub-dimensions with 4 (four) possible categories of assessment results: Strong, Good, Fair, and Weak. Agenda that can be proposed in Indonesia's G20 presidency in 2023 in the trade sector that are in line with national interests, include: (1) Restoring the Role of the WTO as a World Trade Pillar; (2) Transparency and Monitoring of Trade Policy; (3) Protecting and Responding to Developing Country Challenges; (4) Encouraging Economic Growth through Fiscal Stimulus Policy for SMEs; (5) Evaluation of SMEs Policies; (6) Increasing Digital Data Security in E-Commerce; and (7) Evaluation of Digital Service Tax Application in E-Commerce.